Improvement of accounting of financial results for urban transport enterprises - Гавриленко, Олена Євгенівна (Technology audit and production reserves, 2015)
The features of accounting of financial results in the accounts, according to the methodological requirements are investigated. It is outlined that now accounting of the financial results for urban transport enterprises in Ukraine is carried out strictly on common regulatory rules, not taking into account the specifics of transport enterprises. It is proven the necessity of developing and implementing of guidelines for completing the financial statements at legislatively level that would take into account the peculiarities of financial reporting enterprises of different industries both in national and international standards. It is shown the need for differentiation of accounting of the financial results for the kinds of operations. It is given an own vision of the order of accounting of financial results by activities in the urban transport enterprises and made proposals to improve the structure of the income statement (the statement of comprehensive income). Using the proposed guidelines will increase the reliability of the information for each main and additional items the income statement (the statement of comprehensive income) formation and transparency of the financial results of the various activities of urban transport. Implementation of the results in practice of urban transport enterprises, on the one hand, greatly facilitating drafting this report by accounting department, on the other, provide better meet the needs of external users of financial statements in the information about financial results.